Health problems associated with the wrong use of computers in the city of Baghdad - abduljabbar, abdukhaleq; abd, baqer; shukur, munther (Iraqi National Journal of Nursing Specialties, 2012)
The Research aimed for identification the significant of health problems that occurrences through misused of computer for those whom attaches with more than two hours daily and to identification the nature of demographical characteristics variables and that related variables with using computer. Also to know the level of user’s knowledge for some attaché’s equipment’s and finally creating a new suggested measurement scale for studying health problems that were occurred through misused of computer. Creating questionnaire includes several domains (Social problems – family environment, Social problems – external environment, some health problems attaches with related equipment’s, psychological problems, and health problems related to vision, and health problems concerning with the knowledge’s users of computer) for obtaining the data that improved their validity and reliability which is for the (first time). The main conclusions that achieved is a highly grade of body mass index (BMI) for most users which full in overweight level of the studied sample, and the hard problem resulted mainly by the low level of user’s knowledge for health problems domain as well as the registered of Relatives Deficiency (RD) by the other domains that cannot be neglected when studying the impacts of problems also. Finally two extracted factors were obtained (Suggested named): Socio- psych problems factor and Health – Knowledge Deficiency problems factor which formed the suggested scale of the studied phenomena which is for the first time as far (as we know).